Gambaran Hasil Pengukuran Pupil Distance Menggunakan Pupilometer Digital, PD Meter Manual dan PD Meter Aplikasi - Albina Vilia Fera Dasman; Soraya Arifin; Irwandi Rachman; Andri Senoja (RS Mata Makassar, 2024)
This allows light to enter the eyeball and hit the retina. Thus, the pupil appears black because the light entering the eyeball is absorbed by the retina. The purpose of the study was to determine the description of the results of measuring the pupil distance using a manual PD meter, a PD meter, a GlassifyMe application with a pupilometer. The location of the study was at the Makassar Eye Hospital. The results of the Pupil Distance measurement study using a digital Pupilometer, a manual PD meter, and the GlassifyMe PD meter application were obtained from 70 patients at the Makassar Eye Hospital aged 20-58 years which were carried out in the refraction room in December 2023 - January 2024. of 70 patients while the percentage obtained that (54.29%) gave the same Pupil Distance measurement results, while only (45.71%) gave different Pupil Distance measurement results and the average difference was 0.67%. The similarity of Pupil Distance examination results using the PD Meter Application (GlassifyMe) with the Digital Pupilometer, from 70 patients while the percentage obtained that (58.57%) gave the same Pupil Distance measurement results, while only (41.43%) gave different Pupil Distance measurement results and the average difference was 0.98%.